Gap-Junctional communication between developing Drosophila muscles is essential for their normal development. - Todman, M.G.; Baines, R.A.; Stebbings, L.A.; Davies, J.A.; Bacon, J.P. (Developmental Genetics, 1999)
Recent experiments have demonstrated that a family of proteins, known as the innexins, are structural components of invertebrate gap junctions. The shaking-B (shak-B) locus of Drosophila encodes two members of this emerging family, Shak-B(lethal) and Shak-B(neural). This study focuses on the role of Shak-B gap junctions in the development of embryonic and larval muscle. During embryogenesis, shak-B transcripts are expressed in a subset of the somatic muscles; expression is strong in ventral oblique muscles (VO4-6) but only weak in ventral longitudinals (VL3 and 4). Carboxyfluorescein injected into VO4 of wild-type early stage 16 embryos spreads, via gap junctions, to label adjacent muscles, including VL3 and 4. In shak-B2 embryos (in which the shak-B(neural) function is disrupted), dye injected into VO4 fails to spread into other muscles. In the first instar larva, when dye coupling between muscles is no longer present, another effect of the shak-B2 mutation is revealed by whole-cell voltage clamp. In a calcium-free saline, only two voltage-activated potassium currents are present in wild-type muscles; a fast IA and a slow IK current. In shak-B2 larvae, these two currents are significantly reduced in magnitude in VO4 and 5, but remain normal in VL3. Expression of shak-B(neural) in a shak-B2 background fully rescues both dye coupling in embryonic muscle and whole-cell currents in first instar VO4 and 5. Our observations show that Shak-B(neural) is one of a set of embryonic gap-junction proteins, and that it is required for the normal temporal development of potassium currents in some larval muscles.